THE ANALYSIS OF DIAGNOSTIC ASSESSMENT RESULT IN PISA MATHEMATICAL LITERACY BASED ON STUDENTS SELF-EFFICACY IN RME LEARNING - Khaerunisak Khaerunisak; Kartono Kartono; Isti Hidayah; Ahmad Yusril Fahmi (IKIP Siliwangi and I-MES, 2017)
This research aimed to test RME learning with an effective scientific approach to improving mathematical literacy and self-efficacy, obtaining an overview of the mathematical literacy diagnostic assessment results that has high, medium and low self-efficacy as well as student difficulties in learning RME with a scientific approach. This research using mix method concurrent embedded with the subject of research is students class VIII. The research begins with a mathematical literacy diagnostic assessment and self-efficacy inventory then performed RME learning in experimental class and conventional learning in control class. Quantitative analysis was conducted to test the effectiveness of learning and deepened with the interview as a qualitative analysis. Learning RME with a scientific approach effective is marked by the achievement of classical completeness, the proportion of students' mathematical literacy, self-efficacy and the difference in pre-post students’ mathematical literacy on RME learning better than conventional learning. The results of students’ mathematical literacy diagnostic assessment fit the criteria of self-efficacy students except for medium mathematical literacy that having high self-efficacy. Student difficulties in RME learning with the scientific approach are based on the results of mathematical literacy diagnostic assessment, namely language skills problem, the capacity to understand, create strategies, and create the algorithm.